Current issues in donor health and safety. (July 2013) - Lin, C. K.; So, B. K. L.; Leung, J. N. S.; Wong, H. K.; Lee, C. K.
<x xml:space="preserve">Abstract</x> Blood donation is a rather simple procedure, and most people have done so and feel that they can make it at any time. However, it is not uncommon for the public, blood donors and blood service operators to overlook the health and safety issues that could carry impact to both donors and blood donation. In this short review, we try to present an overview of the interaction between donor health and safety and blood donation in either direction. Strategies have been developed to protect prospective donors from ineligible donation that could affect their health, minimize the risk of blood‐donation‐related adverse reaction and prevent long‐term impact on donors and blood donation.